Methylated SEPTIN9 plasma test for colorectal cancer detection may be applicable to Lynch syndrome. Issue 1 (28th May 2019) - Hitchins, Megan P; Vogelaar, Ingrid P; Brennan, Kevin; Haraldsdottir, Sigurdis; Zhou, Nianmin; Martin, Brock; Alvarez, Rocio; Yuan, Xiaopu; Kim, Sungjin; Guindi, Maha; Hendifar, Andrew E; Kalady, Matthew F; et al.
Abstract : Objective: The plasma-based methylated SEPTIN9 (mSEPT9) is a colorectal cancer (CRC) screening test for adults aged 50–75 years who are at average risk for CRC and have refused colonoscopy or faecal-based screening tests. The applicability of mSEPT9 for high-risk persons with Lynch syndrome (LS), the most common hereditary CRC condition, has not been assessed. This study sought preliminary evidence for the utility of mSEPT9 for CRC detection in LS. Design: Firstly, SEPT9 methylation was measured in LS-associated CRC, advanced adenoma, and subject-matched normal colorectal mucosa tissues by pyrosequencing. Secondly, to detect mSEPT9 as circulating tumor DNA, the plasma-based mSEPT9 test was retrospectively evaluated in LS subjects using the Epi proColon 2.0 CE assay adapted for 1mL plasma using the "1/1 algorithm". LS case groups included 20 peri-surgical cases with acolonoscopy-based diagnosis of CRC (stages I-IV), 13 post-surgical metastatic CRC, and 17 pre-diagnosis cases. The control group comprised 31 cancer-free LS subjects. Results: Differential hypermethylation was found in 97.3% (36/37) of primary CRC and 90.0% (18/20) of advanced adenomas, showing LS-associated neoplasia frequently produce the mSEPT9 biomarker. Sensitivity of plasma mSEPT9 to detect CRC was 70.0% (95% CI, 48%-88%)in cases with a colonoscopy-based CRC diagnosis and 92.3% (95% CI, 64%-100%) inpost-surgical metastatic cases. In pre-diagnosis cases, plasma mSEPT9 was detected within two months prior to colonoscopy-based CRC diagnosis in 3/5 cases. Specificity in controls was 100% (95% CI 89%-100%). Conclusion: These preliminary findings suggest mSEPT9 may demonstrate similar diagnostic performance characteristics in LS as in the average-risk population, warranting a well-powered prospective case–control study.